Report from the kick‐off meeting of the Cochrane Skin Group Core Outcome Set Initiative (CSG‐COUSIN). (1st February 2016) - Schmitt, J.; Deckert, S.; Alam, M.; Apfelbacher, C.; Barbaric, J.; Bauer, A.; Chalmers, J.; Chosidow, O.; Delamere, F.; Doney, E.; Eleftheriadou, V.; Grainge, M.; et al.
Summary: A major obstacle of evidence‐based clinical decision making is the use of nonstandardized, partly untested outcome measurement instruments. Core Outcome Sets (COSs) are currently developed in different medical fields to standardize and improve the selection of outcomes and outcome measurement instruments in clinical trials, in order to pool results of trials or to allow indirect comparison between interventions. A COS is an agreed minimum set of outcomes that should be measured and reported in all clinical trials of a specific disease or trial population. The international, multidisciplinary Cochrane Skin Group Core Outcome Set Initiative (CSG‐COUSIN) aims to develop and implement COSs in dermatology, thus making trial evidence comparable and, herewith, more useful for clinical decision making. The inaugural meeting of CSG‐COUSIN was held on 17–18 March 2015 in Dresden, Germany, as the exclusive theme of the Annual Cochrane Skin Group Meeting. In total, 29 individuals representing a broad mix of different stakeholder groups, professions, skills and perspectives attended. This report provides a description of existing COS initiatives in dermatology, highlights current methodological challenges in COS development, and presents the concept, aims and structure of CSG‐COUSIN.